Fixing feedback revision rules in online markets - Gary E. Bolton; Kevin Breuer; Ben Greiner; Axel Ockenfels (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Feedback withdrawal mechanisms in online markets aim to facilitate the resolution of conflicts during transactions. Yet, frequently used online feedback withdrawal rules are flawed and may backfire by inviting strategic transaction and feedback behavior. Our laboratory experiment shows how a small change in the design of feedback withdrawal rules, allowing unilateral rather than mutual withdrawal, can both reduce incentives for strategic gaming and improve coordination of expectations. This leads to less trading risk, more cooperation, and higher market efficiency.
Keywords: C73; C9; D02; L14; 330; dispute resolution system; market design; reputation; trust